Microstructural Development of Ti-6Al-4V Alloy via Powder Metallurgy and Laser Powder Bed Fusion - Alireza Dareh Baghi; Shahrooz Nafisi; Heike Ebendorff-Heidepriem; Reza Ghomashchi (Metals, 2022)
A detailed study was carried out to gain a better understanding of the microstructural differences between Ti-6Al-4V parts fabricated via the conventional powder metallurgy (PM) and the laser powder bed fusion (L-PBF) 3D printing routes. The parts were compared in terms of the constituent phases in the microstructure and their effects on the micro- and nano-hardness. In L-PBF parts, the microstructure has a single phase of martensitic α′ with hcp crystal structure and acicular laths morphology, transformed from prior parent phase β formed upon solidification of the melt pool. However, for the sintered parts via powder metallurgy, two phases of α and β are noticeable and the microstructure is composed of α grains and α + β Lamellae. The microhardness of L-PBF processed Ti-6Al-4V samples is remarkably higher than that of the PM samples but, surprisingly, the nano-hardness of the bulk martensitic phase α′ (6.3 GPa) is almost the same as α (i.e., 6.2 GPa) in PM samples. This confirms the rapid cooling of the β phase does not have any effect on the hardening of the bulk martensitic hcp α′. The high microhardness of L-PBF parts is due to the fine lath morphology of α′, with a large concentration of low angle boundaries of α′. Furthermore, it is revealed that for the α phase in PM samples, a higher level of vanadium concentration lowers the nano-hardness of the α phase. In addition, as expected, the compacting pressure and sintering temperature during the PM process led to variations in the porosity level as well as the microstructural morphology of the fabricated specimens, which will in turn have a significant effect on the mechanical properties.